Modern Approaches To The Study Of Political Processes In Uzbekistan And Their Analysis - U.Hayitov (International Journal of Advanced Science and Technology, 2020)
The article deals with the study of political processes, theories and views on the analysis of its features in Uzbekistan, as well as some issues of using systematic, structural-functional, institutional, situational, procedural, dialectical and other methods of analysis.